Is Step Down Assessment of Screen-Detected Lesions as Safe as Workup at a Metropolitan Assessment Centre? - Hughes, J.; Jose, D.; Tuch, G.; Fritschi, Lin; Tresham, J.; Wylie, E. (Wiley-Blackwell Publishing Asia, 2014)
Objective: BreastScreen WA offers population mammographic screening via fixed clinics in the metropolitan area and mobile clinics that visit country areas every two years. If an abnormality is suspected following mobile clinic screening, women undergo Step Down Assessment; diagnostic further views are performed at the mobile clinic and if a possibly significant abnormality persists, country women are referred to a Perth Metropolitan Breast Assessment Centre. The purpose of this retrospective cohort study was to determine if Step Down Assessment in country Western Australia offered the same diagnostic effectiveness as screening and assessment in the metropolitan area. Methods: The study included all screening episodes at BreastScreen WA between 1999 and 2008. Screening episodes from metropolitan and mobile clinics were compared according to the primary outcomes of cancer detection rates, recall and further investigations, cancer size, return to screen rates and interval cancers. Results: Cancer detection rate per 1,000 screening episodes was lower for the country program than the metropolitan program (3.07 (2.84–3.31) versus 7.04 (6.82–7.27)). The false negative (interval cancer) rate was lower for Step Down Assessment than for the metropolitan program. The size of cancers detected was similar for both screening services. Return to screen rates were comparable between both groups. Conclusion: The results indicate that the current service model is providing appropriate diagnostic effectiveness, as well as comparable client satisfaction, for country and metropolitan women.